The Quintessence of Foods - Shukla, Chetna N.; Sethna, Kamalrukh (Homœopathic Links, 2015)
All food like any other drug has its own state of mind and disposition. It has its own quintessence. Therefore food or eating is not about how many milligrams of fats or carbohydrates or proteins are ingested or how many calories are consumed. It is about mindful eating. It is about eating in tune with Nature. It is not only about seeing food as a superconductor of minerals, vitamins, fats, proteins, carbohydrates, starch and micronutrients but seeing them as superconductors of their own individual character—their quintessence. The food choices you make serve your psyche the way you choose it to serve. If one examines a strong food affinity in the steps given in the case, we can reach the quintessence that particular food imparts to the individual on its consumption.
Keywords: organon on food (§9, 119, 261); food; quintessence; diet and regimen; Rattus rattus